Penerapan Analisis Joint-Space dan Analisis Faktor dalam Persepsi Mahasiswa FMIPA UNMUL terhadap Penggunaan Aplikasi Messenger pada Smartphone - Emi Harmianti; Ika Purnamasari; Memi Nor Hayati (Program Studi Statistika FMIPA Universitas Mulawarman, 2016)
Multidimensional Scaling Analysis (MDS) is a technique that can be used to determine the relative views of respondents to an object which is then represented in a multidimensional map. Joint-Space Analysis is a type of MDS that aims to determine the coordinates of the position of each object and variable pictured together on a map perception (perceptual map). While the factor analysis is a branch of multivariate analysis to determine the factors of concern to respondents. This study aims to determine the position of messenger applications on smartphones based on attributes that are owned, as well as to identify factors that concern respondents in choosing the messenger application based on attributes of the messenger application by the respondents are students FMIPA UNMUL. The data used in this research is primary data from research by spreading the questionnaire with the number of respondents (students FMIPA UNMUL) as many as 100 people. Results from this study indicate that the BlackBerry Messenger application, LINE, WhatsApp best position with all superior attributes that exist within the application.While the application KakaoTalk third place with some excellent attributes of the display, application updates, promotions, connection, performance applications, contacts and groups, stickers and emoticons, as well as account settings. Meanwhile, the Yahoo Messenger application and WeChat is the weakest of applications in a variety of attributes that exist in the messenger application. From the results of the factor analysis, found that there are two factors that concern the consumer in choosing a smartphone messenger app that attribute connections and promotion.